Dark promises - Feehan, Christine (Feehan, Christine. Dark series., 2016)
Gabrielle has had enough of battles, of wars, of seeing the man she's engaged to nearly lose his life when it isn't even his fight. Once Gary was a gentle and very human researcher. Now he's a fearless and lethal Carpathian warrior with the blood of an ancient lineage coursing through his vein--a man Gabrielle still needs and dreams of with every breath she takes. All she wants is a life far away from the Carpathian mountains, far from vampires and the shadows cast by the crumbling monastery that hides so many terrible secrets. But Gabrielle soon learns that promises made in the dark can pierce the heart like a dagger.